(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author describes the beehive-like houses (bothans) found in Lewis and Harris, and compares them to the clochán huts found in Ireland and the brochs on Shetland and Orkney. Although he is interested in their historical usage, he does note that some of these dwellings were still used in the nineteenth century. The article focuses on the structure and features present in these dwellings. There is also some discussion of the folklore of the Each-uisge, a shape-shifting horse creature that appears in several legends about young women living in such dwellings.